الأليات الوقائية والردعية لمكافحة الفساد في الشريعة الإسلامية و التشريع الجزائري (Revue El-Wahat pour les Recherches et les Etudes, 2021)
Corruption Is A Phenomenon That Is One Of The Most Important Challenges Faced By Societies, Which Have Been Exhausted And Are Still Burdening Many Countries, Causing Losses And Effects That Harm The Citizens And The State Alike. As An Attempt To Reduce This Phenomenon, This Research Comes To Uncover And Identify The Preventive And Deterrent Mechanisms The Algerian Legislator And The Corresponding Islamic Law Had Put In Order To Reduce This Phenomenon, And The Research Reached To A Result That Recommends To Follow The Provisions Of Islamic Law And Reconsider The Criminal Policy Applied To The Crimes Of Corruption. Key Words -Fighting Corruption - Preventive Mechanisms - Deterrent Mechanisms